Study Of Protein Carbonyl Group, Nitric Oxide and MDA (Index of Lipid Peroxidation) As Biomarkers of Oxidative Stress in Type 2 Diabetes Mellitus - Chavan, Vilas U; Melinkeri, R R (National Journal of Community Medicine, 2013)
Background: Diabetes mellitus (DM) is metabolic disorders characterized by hyperglycemia and abnormalities in lipid and protein metabolism. The free radicals and oxidative stress may act as a common pathway to diabetes itself, as well as to its later complications. Objectives: The present study was planned to study the biomarkers of oxidative stress, such as protein carbonyl (CO) group, nitric oxide (NO.) in the form of total nitrite (NOx) and malondialdehyde (MDA) as an index of lipid peroxidation in type 2 DM patients and healthy individuals. Methodology: We studied 60 cases of type 2 DM and 30 healthy individuals as control. Serum protein carbonyl estimated by dinitrophenyl hydrazine (DNPH) method, nitrate (NO3-) and nitrite (NO2- ) concentrations in terms of total nitrites (NOx) by Griess reaction and MDA by thiobarbituric acid reagent test. Results: We found highly significant increase in the level (Mean ± SD) of protein carbonyl (3.28 ± 0.75 nmol/mg), NOx (total nitrites) (176 ± 68.12 mmol/L) and MDA (8.3 ± 1.19 nmol/ml) in type 2 DM patients compared to healthy subjects (1.51 ± 0.22 nmol/mg), (46.6 ± 17.5 mmol/L) and (3.12 ± 0.77 nmol/ml) respectively (P < 0.0001). Conclusion: Biomarkers of oxidative stress such as protein carbonyl, NOx (total nitrites) and MDA are significantly increased in type 2 DM compared to healthy subjects. There is increased protein oxidation, lipid peroxidation, and increased conversion of NO. to its end products like nitrite and nitrates in type 2 DM. This suggests that there is increased production of reactive oxygen species (ROS) and oxidative stress in type 2 DM patients compared to healthy subjects.